Preserved brains from the Spanish Civil War mass grave (1936) at La Pedraja1, Burgos, Spain. Issue 6 (December 2016) - Serrulla, Fernando; Herrasti, Lourdes; Navarro, Carmen; Cascallana, Jose Luis; Bermejo, Ana Maria; Marquez-Grant, Nicholas; Etxeberria, Francisco
Abstract: During the excavation of the Spanish Civil War mass grave at La Pedraja (Burgos, Spain), 104 individuals were found interred within it, 45 of which displayed brains that were preserved but dehydrated and reduced in size. This exceptional finding has resulted in the formation of a multidisciplinary team, with the aim of obtaining as much information as possible and to primarily understand the taphonomic phenomena that has led to the preservation of these brains. The following types of analyses were undertaken on three of these brains: macroscopy, histology, radiology, chemical-toxicology, genetics, chemical analysis of the soil and 3D modelling for stereolithography. The historical context was considered, plus all archaeological and other forensic data provided by the investigation of the mass grave. The results of the analyses on these morphologically identifiable human brains confirmed the presence of nerve structures, fatty acids, and in one case ante-mortem evidence for an intracranial haemorrhage. The fatty acid profile corresponds to the process of saponification. Therefore, the interpretation is that the preservation of these brains at the mass grave of La Pedraja was due to the saponification process, which was influenced by the manner and cause of death, the chemical composition of the brain, the physicochemical properties of the soil and the meteorological conditions at the time. Highlights: Almost 50% of individuals from a Spanish 1936 mass grave had their brains preserved. Chemical analysis confirms that these brains were preserved by saponification. Three factors influenced brain preservation: microbiological, chemical and physical. A forensic and holistic approach is emphasized for the recovery and analysis of human remains in forensic context.